Dichotomy in temporal and thermal spin correlations observed in the breathing pyrochlore LiGa1−x In x Cr4O8 - S. Lee (Nature Portfolio, 2021)
Abstract A breathing pyrochlore system is predicted to host a variety of quantum spin liquids. Despite tremendous experimental and theoretical efforts, such sought-after states remain elusive as perturbation terms and lattice distortions lead to magnetic order. Here, we utilize bond alternation and disorder to tune a magnetic ground state in the Cr-based breathing pyrochlore LiGa1−x In x Cr4O8. By combining thermodynamic and magnetic resonance techniques, we provide experimental signatures of a spin-liquid-like state in x = 0.8, namely, a nearly T 2-dependent magnetic specific heat and persistent spin dynamics by muon spin relaxation (μSR). Moreover, 7Li NMR, ZF-μSR, and ESR unveil the temporal and thermal dichotomy of spin correlations: a tetramer singlet on a slow time scale vs. a spin-liquid-like state on a fast time scale. Our results showcase that a bond disorder in the breathing pyrochlore offers a promising route to disclose exotic magnetic phases.